Crowdfunding for Academic Projects: A Case in Public Universities of Malaysia - Lau, K. L.; Chew, B. C.; Maliki, A.; Hafizuddin, H. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
This paper analyzed the academic crowdfunding initiatives of public universities in Malaysia. It investigated the effectiveness of academic crowdfunding initiative, focusing on two important issues namely the most critical hurdle that might challenge the crowdfunding initiative, and an overview of the crowdfunding model which could be the strategy to support the academic research funding. A case study of qualitative research method, including semi-structured interview sessions were conducted. The finding yielded that there were five potential challenges and the fraud in crowdfunding was the most critical challenge. Besides, the most suitable crowdfunding model for researchers from public universities of Malaysia was the donation crowdfunding for this model does not include the claim of ownership and it is more suitable for the public universities in Malaysia. This study provides guidelines to academic researchers in the implementation of crowdfunding for their research project and some innovative suggestions to creating the successful crowdfunding campaigns.